2015
DOI: 10.1111/jai.12732
|View full text |Cite
|
Sign up to set email alerts
|

Sperm production of Steidachneridion parahybae (Steindachner 1877) and the effect of hormonal induction throughout one reproductive cycle

Abstract: Summary The present study assessed the semen production and spermatozoa characteristics of Steidachneridion parahybae throughout one reproductive cycle in captivity and the effect of the induction of maturity with carp pituitary extract (CPE). Hence, six semen samples were collected from 26 specimens of S. parahybae. The samples were divided into two groups (non‐induced and induced) and tested between October 2009 and April 2010 (water temperature = 21.85 ± 0.77 and 21.85 ± 0.80°C, respectively, and density 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
6
1
1
Order By: Relevance
“…The sperm production found in this study was higher than the one verified for the same species by Caneppele et al (2015) and the computerized sperm characteristics were higher than the ones verified by Sanches et al (2013) for fresh semen, and by Araújo (2011) for cryopreserved semen. Therefore, the results obtained in this study were considered satisfactory for artificial reproduction carried out in laboratory routines.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The sperm production found in this study was higher than the one verified for the same species by Caneppele et al (2015) and the computerized sperm characteristics were higher than the ones verified by Sanches et al (2013) for fresh semen, and by Araújo (2011) for cryopreserved semen. Therefore, the results obtained in this study were considered satisfactory for artificial reproduction carried out in laboratory routines.…”
Section: Discussioncontrasting
confidence: 72%
“…This is therefore another factor that might influence the values of fertilization rate (Cosson, 2010). Caneppele et al (2015), studying S. parahybae, observed that the time necessary for approximately 50% of the spermatozoa to lose their motility was 38.76±0.74 seconds, and that after around one minute all of them stopped moving. The use of specific activators may ensure longer time of sperm motility for the S. parahybae (Araújo, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we observed that CPE and mGnRHa + MET treatments provoked ovulation in L. friderici, but the lower CPE dose treatment was the unique that provided viable embryos. This pattern of response is unusual mainly because conventional CPE dose (0.5 mg and 5.5 mg/kg, with 12h interval, with some variations) has provided ovulation and viable embryos in many fish species evaluated worldwide (Mylonas et al, 2010) and is the mainly hormonal therapy used for inducing tropical migratory fish ovulation (Caneppele et al, 2015;Souza et al, 2015;Ittzés et al, 2015;Viveiros et al, 2015;Sanches et al, 2016;Pereira et al, 2017;García et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Still in this context, the most commonly protocol used for obtaining viable embryos in South American reophilic species is still the use of carp pituitary extract (CPE) in conventional dose (0.5 and 5.0 mg/kg), which is applied in a generalized way in different species (Carneiro and Mikos, 2008;Caneppele et al, 2015;Souza et al, 2015;Ittzés et al, 2015;Viveiros et al, 2015;Schorer et al, 2016;Pereira et al, 2017). However, the main problem related to the use of CPE is a constant uncertainty and unpredictability of a successful ovulation (Criscuolo-Urbinati et al, 2012;Hainfellner et al, 2012a, b;Pereira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nós temos avançado no entendimento dos aspectos fundamentais da biologia reprodutiva e do desenvolvimento de S. parahybae em cativeiro. Estudos de Caneppele et al (2009) e Honji et al (2013, estabeleceram o protocolo de indução artificial à reprodução de S. parahybae em cativeiro (respectivamente, de reprodutores selvagens e de origem de cativeiro (F1)); desenvolvimento embrionário e larval (Honji et al, 2012a;Lopes et al, 2015), e a qualidade dos gametas de S. parahybae tem sido descrito também (Honji, 2011;Sanches et al, 2013Sanches et al, , 2014Sanches et al, , 2015Caneppele et al, 2015;Okawara et al, 2015). A reprodução dessa espécie em cativeiro ocorre entre novembro e março, apresentando desenvolvimento oocitá-rio sincrônico, no entanto, durante o período reprodutivo apresenta uma desova em diferentes grupos, ou seja, entre os meses de novembro e março, as fêmeas de S. parahybae podem desovar várias vezes durante o período reprodutivo (Honji, 2011).…”
Section: Biologia Básica E Aplicadaunclassified